Character Building MTs Students of Darul Ulum Sayan through Islamic Religious Education - Elviana Yulianti; Ahirul Habib Padilah (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Islamic religious education has a very important role in shaping one's character. The main goal of Islamic religious education is to guide individuals to have good morals and follow religious teachings well. Basically, character building through Islamic religious education includes four main aspects, namely spiritual, intellectual, social, and emotional aspects. The spiritual aspect is related to efforts to strengthen individual faith in Allah SWT and improve the relationship between humans and Allah SWT. The intellectual aspect is related to the development of knowledge and understanding of Islamic religious teachings. The social aspect relates to efforts to strengthen human values ​​and promote justice in social life. The emotional aspect is related to the development of positive attitudes and behaviors, such as honesty, patience, and tolerance.This research will use a qualitative approach and case study method. A qualitative approach is used because this research focuses on the understanding and interpretation of character building through Islamic religious education from the perspectives of parents, teachers and students. The case study method was used because this research studied specific cases regarding the process of character building through Islamic religious education in one school.